Affective Epiphanies: The Aesthetic Relation of Stories in Museum Encounters - Sinner, Anita (Art/Research International, 2021)
This proposition explores the potential of a pedagogy of affect as an arts- based research approach to museum education at the university level. Such an approach is predicated on a continuous movement of situated stories as the heart of the learning encounter, generated relationally between object-body-space, or artwork- learner-museum. As a forum for deliberation, the purpose of this conversation is to consider how emotions, as the basis for teaching with caring and sensory awareness, bring vitality, aliveness, and feelings to the fore. This conversation explores affective epiphanies sourced from personal practical knowledge as an expression of arts- research-in-progress. By drawing on autoethnographic life writing, I explore an alternate approach to three museum collections that demonstrate how and why the aesthetic relation of stories operate as pedagogic pivots in ways that reconfigure conventional museum engagement. Rethinking museum education with an arts research perspective is an effort to advance how context connects affective systems of knowing relationally, and why embracing stories offers new pathways to understand museum education through more expansive learning approaches, inclusive of feeling.